Integrasi Nilai Intelektual dan Spiritual dalam Pendidikan Perspektif Al-Qur’an dan Hadis - Karisma, Intan; Bisyarotul Masfufah; Muhammad Umar Faruq; Abdurrahman (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2026)
Education from an Islamic perspective is a fundamental need regulated by the Qur'an and the Hadith. It is a divinely guided process aimed at holistic human development. A literature review concludes that education encompasses the processes of personality development, knowledge expansion and moral formation. This integrated process serves as essential preparation for fulfilling the trust of vicegerency on Earth. This research employs a qualitative method using literature review and content analysis of key Qur'anic verses and Hadith narrations related to education. The study results indicate that the Qur'an uses various termssuch as tadabbur, tazkiyah, tafaqqquh, and al-hidayah to emphasize the necessity of deep, transformational learning. This learning instills wisdom and conviction, going beyond mere memorization. Concurrently, the Hadith explicitly affirms the obligation to seek knowledge (talab al-ilm) for every Muslim, regardless of gender. The Hadith also stresses the immense benefits of scholarship, specifically including beneficial knowledge-based deeds, which serve as a continuous charity. The resultant conceptual synchronization between these primary sources affirms that the urgency of education in Islam is centered on molding individuals who are both highly knowledgeable and possess noble character. Such individuals are prepared to carry out their interdependent roles of worship and vicegerency (khalifah) according to the guidance and moral framework of the Shari'ah.